The Complexity of College Readiness: Differences by Race and College Selectivity. (August 2018) - Klasik, Daniel; Strayhorn, Terrell L.
To make the abstract idea of "college readiness" legible for public purposes, readiness indicators have tended to treat students identically: If a student meets a simple benchmark, he or she is ready for any college. This shorthand ignores that indicators of readiness may differ according to students' backgrounds and where they choose to enroll in college. We use nationally representative data to show that readiness measures that are sensitive to students' race/ethnicity and the selectivity and level of colleges in which they enroll reveal important nuance in readiness predictions. We find different readiness benchmarks indicate readiness for different groups of students when high school performance measures are used to predict different college outcomes, complicating the interpretation and use of conventional readiness measures.